Supramolecular design in 2D covalent organic frameworks. (19th February 2020) - Alahakoon, Sampath B.; Diwakara, Shashini D.; Thompson, Christina M.; Smaldone, Ronald A.
Abstract : 2D covalent organic frameworks (COFs) are a class of porous polymers with crystalline structures. This tutorial review discusses how the concepts of supramolecular chemistry are used to add form and function to COFs through their non-covalent bonds. Abstract : 2D covalent organic frameworks (COFs) are a class of porous polymers with highly crystalline structures and tunable function. The structure of a 2D-COF consists of two dimensional sheets held together through covalent bonds which are then stacked together through non-covalent forces. Since their first report, the synthesis of new COFs has relied mostly on imparting functionality to the monomer structures through covalent modification, or through the use of new thermodynamically controlled covalent bond forming methods. This tutorial review will discuss recent efforts to use supramolecular design to leverage the non-covalent forces between COF monomers and sheets to improve their properties and function. The importance of supramolecular interactions in COFs to their mechanisms of formation and overall structure will also be covered.